NEW GENERATION OF REGIONAL UNIVERSITIES IN RUSSIA - Ovchinnikova, Nataliia; Ovchinnikova, Oksana; Kolmykova, Tatiana; Bredikhin, Vladimir (Journal of Applied Engineering Science, 2018)
The regionalization of economic processes associated with digital transformation actualized the issue of the universities influence on the industrial development of the territories. The Russian industry has a significant gap from the industries of the developed countries, which raised the issue of the necessity of the introduction of new technologies, new knowledge and the transformation of the traditional industry. The process of supporting the leading regional universities began in Russia with the aim of activating their interaction with the region's industry. The article analyzes the socio-economic situation of the regions, in which flagship universities receive government support. The main objective of such universities is the university-industry interaction in the sphere of new knowledge and technologies. The authors analyzed socio-economic factors that encouraged regional universities to participate in the flagship universities project competitive selection. The article alalyses the first eleven universities that have become flagship in this project. The authors presented a regional university –industry interaction model. The article focuses on two forms of such cooperation: direct cooperation and triangle cooperation (university-industry-government). Over the past two years the realization of the project «flagship university» shows great results. More than 70% of flagship universities became the active partners of regional industry and pushed increase of the regional economy. Moreover, this article puts a start to a large research about the university-industry interaction, especially in the engineering universities. The main problems and barriers of university-industry interaction in Russia are determined in the article.
Keywords: innovations; higher education; triple helix; engineering universities; university-industry interaction; regional development